Food intake among smallholder cassava value chain households - Samuel, F.O.; Akinwande, B.A.; Opasola, R.O.; Azeez, L.A.; Abass, A. (Emerald Publishing Limited, 2019)
Purpose The purpose of this study is to compare food consumption and dietary diversity in smallholder cassava value chain households (CVCHs) and non-cassava value chain households (non-CVCHs).